PENGGUNAAN MEREK ONITSUKA TIGER OLEH AKUN TANPA CENTANG BIRU @ONITSUKATIGERR_INDONESIA BERDASARKAN UNDANG – UNDANG NOMOR 20 TAHUN 2016 TENTANG MEREK DAN INDIKASI GEOGRAFIS: Use of the Onitsuka Tiger Mark by Accounts Without a Blue Checkmark @Onitsukatigerr_Indonesia Based on Law Number 20 of 2016 Concerning Trademarks and Geographical Indications - Putri, Dian Riyanti Pramudya; Desmayanti, Rakhmita (Faculty of Law, Universitas Trisakti, 2024)
A brand is a sign to differentiate one good/service from another, protected under Article 3 of Law No. 20 of 2016 concerning Marks and Geographical Indications. How to protect the rights holders of the Onitsuka Tiger brand, which are used by other parties without rights based on Law No. 20 of 2016 concerning Trademarks and Geographical Indications, and what is the law regarding sales made by account holders without blue ticks who use other parties' brands without rights on Instagram is the main problem in this thesis. The type of research used is normative, which is analyzed qualitatively, with primary and secondary data as sources of information. Research findings indicate (1) Legal protection for registered trademark owners to protect their trademarks from fraudulent or detrimental actions from other business actors is stated in Article 21 Paragraph (1) and Paragraph (3) of the Trademark Law,Instagram, Instagram will only deactivate the violator's account and is not responsible for any losses experienced by the owner of the registered mark.